Sensitivity and specificity of standardised allergen extracts in skin prick test for diagnoses of IgE-mediated respiratory allergies - Wagner, Nicola; Rudert, Michael (Clinical and Translational Allergy, 2019)
Background: Skin prick tests (SPTs) are essential for the diagnosis of IgE-mediated allergy and are influenced by extract quality, biological potency and concentration of allergen.
CRIS-Team WoS Importer:2019-03-26